2016
DOI: 10.1038/srep37458
|View full text |Cite
|
Sign up to set email alerts
|

Natural zwitterionic betaine enables cells to survive ultrarapid cryopreservation

Abstract: Cryoprotectants (CPAs) play a critical role in cryopreservation because they can resist the cell damage caused by the freezing process. Current state-of-the-art CPAs are mainly based on an organic solvent dimethyl sulfoxide (DMSO), and several DMSO-cryopreserved cell products have been brought to market. However, the intrinsic toxicity and complex freezing protocol of DMSO still remain as the bottleneck of the wide use for clinical applications. Herein, we reported that betaine, a natural zwitterionic molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 46 publications
4
87
1
Order By: Relevance
“…Similarly, Sharp et al observed lower cell densities after 24 h compared to immediately post-thaw. 40 Yang and co-workers measured cell survival over time (after cryopreservation) and found it peaked at 1–2 h post-thaw but decreased after 24 h incubation, 41 highlighting that immediate post-thaw measurements lead to significant overestimation of cryoprotectant activity. Mercado et al showed that adding an amphiphilic polymer to SAOS-2 cells along with 200 mM trehalose gave a cryoprotective benefit but found significant differences between the two assessment methods (trypan blue and MTS assay) when the cells were analyzed immediately post-thaw.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sharp et al observed lower cell densities after 24 h compared to immediately post-thaw. 40 Yang and co-workers measured cell survival over time (after cryopreservation) and found it peaked at 1–2 h post-thaw but decreased after 24 h incubation, 41 highlighting that immediate post-thaw measurements lead to significant overestimation of cryoprotectant activity. Mercado et al showed that adding an amphiphilic polymer to SAOS-2 cells along with 200 mM trehalose gave a cryoprotective benefit but found significant differences between the two assessment methods (trypan blue and MTS assay) when the cells were analyzed immediately post-thaw.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Wang et al .’s work shows embryos would be arrested in the late of 2-cell stage when they are stressed by physiological osmolarity in the absence of organic osmolytes 43 . Besides above, being a natural zwitterionic molecule, betaine had been found to serve as a nontoxic and high efficient cryoprotectant for it presented negligible cytotoxicity even after long-term exposure of cells 44 . But, our study seems not to support this hypothesis of betaine protecting embryos against ethanol by regulating osmolarity in that glycine did not function as expected in this study, although it had been proven that glycine could participate in the process of osmolarity regulation in vitrification of mouse GV oocytes 30 .…”
Section: Discussionmentioning
confidence: 99%
“…CB has been used in a range of biotechnological applications, above all as cryoprotectant [8,9]. It has been suggested that this modified amino acid has the capacity to form hydrogen bonds with a range of organic and inorganic acids that are likely to be responsible for the ascertained CB properties in supporting the adhesion and proliferation of several types of cells [10][11][12].…”
Section: Introductionmentioning
confidence: 99%